Applying Rosenblatt’s Reader-Response Theory to The Yellow Wallpaper - Ginting, Hestika (English Education Study Program FKIP Universitas Alwashliyah Medan, 2025)
This study applies Rosenblatt’s Reader-Response Theory to Charlotte Perkins Gilman’s The Yellow Wallpaper, examining how individual readers understand and connect with the literary text through personal experiences and knowledge. Using a qualitative methodology involving questionnaire and interviews, the research gathers responses from 15 students of English Literature to explore interpretations of the story’s theme, particularly mental health, gender roles, and autonomy. The findings shows that students are able to express their Affective responses, Associative responses, Reflective responses, Interpretive responses and Inferential responses. The study further demonstrates that the Reader- Response Approach has helped the students to understand the literary text by showing empathy, critical thinking, and active literary engagement.